Комплексний аналіз геохімічного стану придорожніх територій великого міста - Борисов, Олександр Олександрович; Кофанова, Олена Вікторівна (НТУ "ХПІ", 2017)
Проаналізовано вплив шкідливих домішок в атмосферному повітрі великих міст на здоров’я людей, визначено внесок автотранспорту у забруднення навколишнього міського середовища та у зміни клімату на планеті. Зроблено висновок щодо необхідності комплексного геоекологічного аналізу стану міських територій та зелених насаджень, розташованих поблизу доріг і автомагістралей. Проведена оцінка кислотно-сольового забруднення атмосферних опадів та придорожніх ґрунтів у м. Києві. Встановлено кореляційні залежності між кислотним та сольовим забрудненням придорожньої території великого міста, досліджено сезонну динаміку забруднень. Встановлено, що використання протиожеледних засобів узимку суттєво впливає на якість ґрунтів та, як наслідок, на стан та розвиток зелених насаджень. Розраховано комплексний показник геохімічного забруднення досліджуваних територій.

Actuality of the work is determined by the growing anthropogenic pressure on the environment of the urban areas and by the increase of the health problems of the urban population. The aim of the scientific investigation was to analyze and comprehensively estimate the geoecological state of the roadside urban territories, identify the main pollutants and their sources of formation, as well as the factors that have the greatest impact on the distribution of harmful substances and on the degree of the pollution of the territories. Data processing was performed with the help of the statistical methods using Microsoft Office Excel and SPSS Statistics software. Calculations of mean values, measurement errors, two-factor regression analysis, as well as charts and histograms were made with the help of the Microsoft Office Excel. In the article, the influence of the harmful pollutants in the air of the cities on the human health was analyzed; the contribution of the motor transport to the contamination of the urban environment and climate change was determined. The conclusion about the necessity of the complex geoecological analysis of the state of the urban territories and green spaces located near roads and highways was made. Estimation of the acid and salt contamination of the atmospheric precipitation and roadside soils in Kyiv was performed. Correlation dependencies between acid and salt contamination of the roadside areas of the city were found; seasonal dynamics of the pollution was investigated. It was determined that the use of the deicing agents in winter significantly affects the quality of soils and, consequently, affects the state and development of green spaces. The complex index of the geochemical pollution of the studied territories was calculated.
Complex analysis of the geochemical state of the city roadside areas
Keywords: екологічна безпека; забруднення атмосферного повітря; автотранспортне забруднення; кислотно-сольове забруднення ґрунтів; зелені насадження; environmental safety; air pollution; automobile pollution; geochemical state